Predicting the Settlement of Mine Waste Dump Using Multi-Source Remote Sensing and a Secondary Consolidation Model - Tabish, Reza; Yang, Zefa; Wu, Lixin; Xu, Zhihua; Cao, Zhanpeng; Zheng, Kaihui; Zhang, Yanqing (Frontiers in Environmental Science, 2022)
The settlement (or subsidence) of mine waste dump is likely to cause landslides, thereby imposing threats on the safety of human beings and other local properties. Hence, it is essential to accurately predict the settlement for the early-warning of settlement-induced geohazards. Traditional mechanical methods require in situ mechanical parameters and the geological structure of mine waste dump, narrowing their practical applications. In this paper, we proposed a remote sensing-based method for predicting the settlement of mine waste dump without the requirement for field observations. Firstly, the historical settlement and thickness of mine waste dump were measured by space-borne interferometric synthetic aperture radar (InSAR) and photogrammetry techniques, respectively. Secondly, the temporal evolution of the settlement of mine waste dump was described by a secondary consolidation model. Thirdly, the parameters of the secondary consolidation model were inverted based on the InSAR-measured historical settlements and photogrammetry-estimated thickness. Finally, the evolution trend of the settlement of the mine waste dump was predicted with the secondary consolidation model and its inverted parameters. The proposed method was tested over a mine waste dump in Weijiamao open-pit mine, China. The result shows that the root mean square error of the predicted time-series settlement is about 0.8 cm. The presented method will be beneficial to the assessment and early-warning of the settlement-related geohazards of mine waste dumps over a large area.